SOME ASPECTS IN EQUIPPING TOURISM MAPS (Academicia Globe: Inderscience Research, 2022)
In this article, the main printing methods for the development, equipment and selection of cartographic imaging methods for the content of Tourism maps, as well as the design of conditional signs for tourism cartographic works are considered.